Denitrification and Biodiversity of Denitrifiers in a High-Mountain Mediterranean Lake - Castellano-Hinojosa, Antonio; Correa-Galeote, David; Carrillo, Presentación; Bedmar, Eulogio J.; Medina-Sánchez, Juan M. (Frontiers in Microbiology, 2017)
Wet deposition of reactive nitrogen (Nr) species is considered a main factor contributing to N inputs, of which nitrate (NO3-) is usually the major component. The microbial group of denitrifiers are largely responsible for reduction of nitrate to molecular dinitrogen (N2) in terrestrial and aquatic ecosystems, but the role of denitrification in removal of contaminant nitrates in high-mountain lakes is not well understood. We have used the oligotrophic, high-altitude La Caldera lake in the Sierra Nevada range (Spain) as a model to study the role of denitrification in nitrate removal. Dissolved inorganic nitrogen concentration in the water column of la Caldera, mainly nitrate, decreased over the ice-free season which was not associated with growth of microbial plankton or variations in the UVR radiation. Denitrification activity, estimated as nitrous oxide (N2O) production, was measured in the water column and in sediments of the lake, and had maximal values in the month of August. Relative abundance of denitrifying bacteria in sediments was studied by quantifying (qPCR) the 16S rRNA and the two phylogenetically distinct clades nosZI and nosZII genes encoding nitrous oxide reductases. Diversity of denitrifiers in sediments was assessed using a culture-dependent approach and after the construction of clone libraries employing the nosZI gene as a molecular marker. In addition to genera Polymorphum, Paracoccus, Azospirillum, Pseudomonas, Hyphomicrobium, Thauera and Methylophaga, which were present in the clone libraries, Arthrobacter, Burkholderia and Rhizobium were also detected in culture media that were not found in the clone libraries. Analysis of biological activities involved in the C, N, P and S cycles from sediments revealed that nitrate was not a limiting nutrient in the lake, allowed N2O production and determined denitrifiers’ community structure. All these results indicate that denitrification could be a major biochemical process responsible for the N losses that occur in La Caldera lake.